Y = ax + 4x - 2 x= 1
y = a(1) + 4(1) -2
y = a + 2
y - 2 = a
Answer:
length is (-7,-1) and radius is 6
Step-by-step explanation:
We are given the expression of the equation of a circle that is
x2 + y2 + 14x + 2y + 14 = 0.
Using completing the squares:
x2 + y2 + 14x + 2y + 14 = 0(x+7)^2 + (y+1) ^2 = -14 + 49 + 1(x+7)^2 + (y+1) ^2 = 36 center thus is at (-7,-1) and the radius is equal to square root of 36 equal to 6.
Step-by-step explanation:
cho f(t)=(t-4)u(t-2)phep bien doi laplace la
F(s)=e^-2s/s^2-2e^-2s/s62